2017
DOI: 10.1590/1414-431x20176424
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of brain-derived neurotrophic factor and cortisol in healthy heavy smokers

Abstract: Studies suggest that brain-derived neurotrophic factor (BDNF) and the hypothalamic-pituitary-adrenal (HPA) axis modulate dopaminergic activity in response to nicotine and that the concentrations of BDNF and cortisol seem to be dependent on the amount and duration of smoking. Therefore, we investigated BDNF and cortisol levels in smokers ranked by daily cigarette consumption. Twenty-seven adult males (13 non-smokers and 14 smokers) participated in the study. The smokers were divided in two groups: light (n=7) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…Smoking and plasma BDNF levels. We did not find any significant difference in plasma BDNF levels of smokers compared to non-smokers; a finding contrary to Neves et al, 22 who reported significantly higher BDNF in heavy smokers compared to non-smokers. The underlying cause of discrepancy could be due to the possibility that our study participants were lightsmokers and not the heavy-smokers.…”
Section: Discussioncontrasting
confidence: 99%
“…Smoking and plasma BDNF levels. We did not find any significant difference in plasma BDNF levels of smokers compared to non-smokers; a finding contrary to Neves et al, 22 who reported significantly higher BDNF in heavy smokers compared to non-smokers. The underlying cause of discrepancy could be due to the possibility that our study participants were lightsmokers and not the heavy-smokers.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, six studies have been conducted in humans to determine the effects of nicotine (via cigarette smoking) on peripheral BDNF levels (summarised in Table 1). From these studies, the predominant direction of change due to nicotine exposure is increased BDNF (Zhang et al, 2010, Suriyaprom et al, 2013, Jamal et al, 2015, Neves et al, 2017. The initial two studies performed by Kim et al and Bhang et al were performed on plasma with relatively small sample size and showed that healthy adult smokers had decreased plasma BDNF than the non-smokers; when smoking was ceased for > 4 weeks, BDNF levels increased to the non-smoker's levels or above (Kim et al, 2007, Bhang et al, 2010.…”
Section: Human Studies Of Nicotine On Bdnf and Trkbmentioning
confidence: 99%
“…The initial two studies performed by Kim et al and Bhang et al were performed on plasma with relatively small sample size and showed that healthy adult smokers had decreased plasma BDNF than the non-smokers; when smoking was ceased for > 4 weeks, BDNF levels increased to the non-smoker's levels or above (Kim et al, 2007, Bhang et al, 2010. The subsequent studies performed on serum with larger sample size showed that both schizophrenic (Zhang et al, 2010) and healthy adults (Suriyaprom et al, 2013, Jamal et al, 2015, Neves et al, 2017 had increased serum BDNF levels and this was associated /correlated with the amount and duration of cigarette smoking and blood cortisol levels, but not with the BDNF Val66Met genotype (Suriyaprom et al, 2013). Combined, these studies provide strong evidence that nicotine exposure in humans affects BDNF expression and this is most likely to be a consequence of the changes in brain BDNF levels, something that animal studies have helped to clarify as discussed in the next section.…”
Section: Human Studies Of Nicotine On Bdnf and Trkbmentioning
confidence: 99%
“…Most studies have provided strong evidence showing that exposure to nicotine leads to increased brain BDNF levels (Zhang et al, 2010;Suriyaprom et al, 2013;Jamal et al, 2015;Neves et al, 2017; for review, see Machaalani and Chen, 2018). The expression of BDNF and its tyrosine kinase receptor B receptor are linked to a7nAChRs where evidence shows BDNF and nAChRs mutually influencing each other (Freedman et al, 1993;.…”
Section: Discussionmentioning
confidence: 99%